Antisemitismus zwischen Latenz und Leidenschaft : Kommunikations- und Äußerungsformen des Judenhasses im Wandel - Borsch, Andreas (2024)
Antisemitism as a passionate (re)interpretation of the world has been resonating beyond the circle of the "usual suspects" in right-wing extremism since before October 7th 2023. This volume explores the persistence, adaptability and global spread of anti-Jewish ideas and manifestations and traces them from antiquity to the Telegram chats, university auditoriums and cultural institutions of the contemporary world.